Systematic review of educational interventions to improve the menstrual health of young adolescent girls - Frances Griffiths; Bronwyn Harris; Chinwe Onuegbu; Rebecca Lane Evans (BMJ Open)
Objectives To systematically review interventions that include an element of menstrual education delivered to young adolescent girls.Design This was a systematic review and meta-analysis. Selected articles were quality assessed using the Mixed Methods Appraisal Tool quality appraisal checklist. A meta-analysis was conducted on a subset of articles, and the effect size of the intervention was calculated using Cohen’s d. A logic model was constructed to frame the effect of menstrual education interventions on menstrual health.Setting Papers reporting on interventions in high-income and low-income and middle-income countries were sought.Information sources Seven electronic databases were searched for English-language entries that were published between January 2014 and May 2020.Participants The interventions were aimed at younger adolescent girls aged 10–14 years old.Interventions The interventions were designed to improve the menstrual health of the recipients, by addressing one or more elements of menstrual knowledge, attitude or practices (KAP).Eligibility criteria Interventions that had not been evaluated were excluded.Primary and secondary outcomes The most common type of output was a difference in knowledge or skill score ascertained from a pre and post test. Some studies measured additional outcomes, such as attitude or confidence.Results Twenty-four eligible studies were identified. The number of participants varied from 1 to 2564. All studies reported improvements in menstrual KAP. The meta-analysis indicates that larger effect sizes were attained by those that encouraged discussion than those that distributed pamphlets.Conclusions Education interventions are effective in increasing the menstrual knowledge of young adolescent girls and skills training improves competency to manage menstruation more hygienically and comfortably. Interactive interventions are more motivating than didactic or written. Sharing concerns gives girls confidence and helps them to gain agency on the path to menstrual health.Trial registration number For this review, a protocol was not prepared or registered.